2022
DOI: 10.2147/opth.s387034
|View full text |Cite
|
Sign up to set email alerts
|

Motorcycle-Associated Ocular Injuries: A Narrative Review

Abstract: Purpose Motorcycle-related injuries involving the eye and orbit are not well characterized, with a paucity of prospective studies focusing specifically on motorcycle-associated eye injuries nor literature reviews having been conducted on the subject. To better understand the injury types and descriptive characteristics of patients experiencing motorcycle-associated eye injuries, we sought to conduct a narrative review. Methods The research team utilized the following da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
1
2
0
Order By: Relevance
“…Ocular injuries resulting from motorcycle accidents can range from mild to severe and can have lasting effects on vision; motorcycle accidents often expose riders to various types of impact debris and forces that can directly or indirectly lead to ocular injuries. 4 The age and sex distribution in the current study were in agreement with the results of Larona and Pe-Yan (2012), as they studied 34 cases of motorcycle ocular injuries and reported a mean of 27.1 years, and 88.2% of their study sample was composed of males. 23 Hsieh et al (2017) reported that 6,072 were admitted due to motorcycle injuries, 994 (16.4%) of them were ≥ 65 years, and 5078 (83.6%) were aged between 20-64 years; however, females formed 41.9% of the elderly and 42.9% of adults.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Ocular injuries resulting from motorcycle accidents can range from mild to severe and can have lasting effects on vision; motorcycle accidents often expose riders to various types of impact debris and forces that can directly or indirectly lead to ocular injuries. 4 The age and sex distribution in the current study were in agreement with the results of Larona and Pe-Yan (2012), as they studied 34 cases of motorcycle ocular injuries and reported a mean of 27.1 years, and 88.2% of their study sample was composed of males. 23 Hsieh et al (2017) reported that 6,072 were admitted due to motorcycle injuries, 994 (16.4%) of them were ≥ 65 years, and 5078 (83.6%) were aged between 20-64 years; however, females formed 41.9% of the elderly and 42.9% of adults.…”
Section: Discussionsupporting
confidence: 91%
“…26 To the best of our knowledge, no study directly reported open globe injury due to motorcycle injury, rather aggregated road traffic accidents cases, Upaphong et al (2021) reported that motorcycle injuries constituted 56.3% of patients aged <20 years, 25% (age 20-39 years), 15% (aged 40-59 years), and 20% (age >60 years), and in all patients, hyphema were seen in 55.4%, lens injuries (52.5%), and uveal prolapse (55.4%). 27 In a review done by it was reported that blowout fractures were the third observed mechanism for orbital fractures, 28 Also other studies reported that motorcycle accidents were the leading cause of orbital/ facial fractures. 29,30 Direct contact between the eye and a chemical (e.g., gasoline), or even chemical fumes, can cause burns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation